DETERMINATION OF MECHANISMS FOR THE IMPLEMENTATION OF LEGAL MONITORING FOR COMPLIANCE WITH NATIONAL INTERESTS IN ACCORDANCE WITH CURRENT REGULATORY LEGAL ACTS (Journal of actual problems of jurisprudence, 2024)
The collective article discusses the issues of improving the mechanism of legal monitoring of regulatory legal acts of Kazakhstan. When conducting legal monitoring, state bodies, in accordance with regulatory requirements, have the right to involve public and scientific organizations, citizens in accordance with the procedure established by the legislation of the Republic of Kazakhstan. And it is imperative to involve appropriate qualified researchers. In this case, only deep, systematic scientific research can determine the negative consequences of law-making, the subject of which is directly the requirements for ensuring national security.Scientific research on topical legal problems of Kazakhstan has been conducted and is being conducted in research institutes and higher educational institutions of Kazakhstan, which have revealed the shortcomings of the institute of legal monitoring.  Using the example of the analysis of the Code of the Republic of Kazakhstan "On Health and the Healthcare system" and the "Water Code of the Republic of Kazakhstan", the necessity of inclusion in scientific expert legal analysis as a mandatory element in conducting legal monitoring expertise in terms of substantiation of ensuring and observing the national interests of the Republic of Kazakhstan is justified.Keywords. Legal monitoring, regulatory legal acts, national interests, corruption norms, water legislation, healthcare, population, scientific research.